Development and validation of a risk score for predicting pericardial effusion in patients undergoing leadless pacemaker implantation: experience with the Micra transcatheter pacemaker. Issue 7 (13th January 2022) - Piccini, Jonathan P; Cunnane, Ryan; Steffel, Jan; El-Chami, Mikhael F; Reynolds, Dwight; Roberts, Paul R; Soejima, Kyoko; Steinwender, Clemens; Garweg, Christophe; Chinitz, Larry; Ellis, Christopher R; Stromberg, Kurt; et al.
Abstract: Aims: There is limited information on what clinical factors are associated with the development of pericardial effusion after leadless pacemaker implantation. We sought to determine predictors of and to develop a risk score for pericardial effusion in patients undergoing Micra leadless pacemaker implantation attempt. Methods and results: Patients ( n = 2817) undergoing implant attempt from the Micra global trials were analysed. Characteristics were compared between patients with and without pericardial effusion (including cardiac perforation and tamponade). A risk score for pericardial effusion was developed from 18 pre-procedural clinical variables using lasso logistic regression. Internal validation and future prediction performance were estimated using bootstrap resampling. The scoring system was also externally validated using data from the Micra Acute Performance European and Middle East (MAP EMEA) registry. There were 32 patients with a pericardial effusion [1.1%, 95% confidence interval (CI): 0.8–1.6%]. Following lasso logistic regression, 11 of 18 variables remained in the model from which point values were assigned. The C -index was 0.79 (95% CI: 0.71–0.88). Patient risk score profile ranged from −4 (lowest risk) to 5 (highest risk) with 71.8% patients considered low risk (risk score ≤0), 16.6% considered medium risk (risk score = 1), and 11.7% considered high risk (risk score ≥2) for effusion. The median C -index following bootstrap validation was 0.73 (interquartile range: 0.70–0.75). The C -index based on 9 pericardial effusions from the 928 patients in the MAP EMEA registry was 0.68 (95% CI: 0.52–0.83). The pericardial effusion rate increased significantly with additional Micra deployments in medium-risk ( P = 0.034) and high-risk ( P < 0.001) patients. Conclusion: The overall rate of pericardial effusion following Micra implantation attempt is 1.1% and has decreased over time. The risk of pericardial effusion after Micra implant attempt can be predicted using pre-procedural clinical characteristics with reasonable discrimination. Clinical trial registration: The Micra Post-Approval Registry (ClinicalTrials.gov identifier: NCT02536118), Micra Continued Access Study (ClinicalTrials.gov identifier: NCT02488681), and Micra Transcatheter Pacing Study (ClinicalTrials.gov identifier: NCT02004873).